(untitled) (International Current Pharmaceutical Journal, 2015)
The present work was carried out to study the disintegrant property of plantago ovata mucilage. The objective of the work was to formulate Fast disintegrating tablets of Domperidon with a view to enhance patient compliances and dissolution rate by direct compression method using 3² full factorial design. Plantago ovata mucilage (2-10% w/w) was used as natural superdisintegrant and microcrystalline cellulose (0-30% w/w) was used as diluent, along with directly compressible mannitol to enhance mouth feel. The tablets were evaluated for hardness, friability, thickness, drug content uniformity, in vitro dispersion time, wetting time and water absorption ratio. Based on in vitro dispersion time (approximately 10s); the formulation containing 10% w/w Plantago ovata mucilage and 30%w/w microcrystalline cellulose was found to be promising and tested for in vitro drug release pattern (in 0.1 N HCl), short-term stability (at 40º/75% RH for 3 month) and drug-excipient interaction. Surface response plots are presented to graphically represent the effect of independent variables (concentrations of Plantago ovata mucilage and microcrystalline cellulose) on the in vitro dispersion time. The validity of the generated mathematical model was tested by preparing two extra-design check point formulations. The optimized tablet formulation was compared with conventional commercial tablet formulation for drug release profiles. This formulation showed nearly four-fold faster drug release (t50% 2.85 min) compared to the conventional commercial tablet formulation (t50% 7.85 min). Short-term stability studies on the formulation indicated that there are no significant changes in drug content and in vitro dispersion time (p < 0.05). Shahidulla et al., International Current Pharmaceutical Journal, July 2015, 4(8): 415-419